Controlling of Absorption and Dispersion Spectrum via Electromagnetically Induced Transparency (Journal of Sciences, Islamic Republic of Iran)
In this paper we examine the absorption and dispersion properties of a weak probe field via Electromagnetically Induced Transparency (EIT) in a four-level system. It is shown that under certain condition, using this model, the absorption cancellation is appeared and the medium becomes transparent to the weak probe field. It will be shown that the controlling of absorption and dispersion spectrum depends on some atomic parameters. The effects of quantum interference on the absorption and dispersion spectrum are also investigated